Allocentric effort decision making : a neuroeconomic investigation - Fitzgerald, Sean (Nanyang Technological University, 2018)
Decisions often require tradeoffs between costs and benefits, such as effort and reward. Prior findings show that decision makers discount the subjective value of a rewarding option as the effort required to obtain it increases. The mechanisms of discounting when the decision maker is also the recipient of the outcome (“egocentric” decision making) are known. However, in many cases, the decision maker decides for someone else, with the decision outcomes delivered entirely to another person (“allocentric” decision making). Implementing a neuroeconomics approach, the present thesis examines the mechanisms of allocentric decisions in the domain of effort discounting across three different levels: behavioral, computational, and neural descriptions of a single phenomenon. Behavioral results showed that making allocentric, as compared to egocentric, effort decisions shifts preferences toward smaller effort, smaller reward options. Computational modeling revealed that differential weighting of effort discounting parameters adequately explained choice differences between allocentric and egocentric decisions. Furthermore, neural activation patterns examined using functional magnetic resonance imaging in brain regions associated with value and reward (the prefrontal cortex and striatum) along with regions associated with theory of mind and social cognition (the temporoparietal junction, posterior cingulate cortex, and angular gyrus) reflected allocentric option valuation, choices, and estimated computational modeling parameters. Together, the research presented in this thesis describes allocentric effort decisions as a discriminant phenomenon, provides computational modeling of how allocentric decision makers value the tradeoff between effort and compensation, and offers physiological evidence of the related cognitive processes.